2008
DOI: 10.1016/j.jhazmat.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 hydrosols with high activity for photocatalytic degradation of formaldehyde in a gaseous phase

Abstract: Two types of TiO2 hydrosols (TOSO and HTO) were prepared from titanium sulfate (TiOSO4) and metatitanic acid (H2TiO3) by a chemical precipitation-peptization method, respectively. The prepared hydrosols were characterized by means of X-ray diffraction, particle size distribution, scanning electron microscopy, UV-vis spectroscopy, Fourier transform infrared spectroscopy, Brunauer-Emmett-Teller and Barret-Joyner-Halender methods. The results showed that the TiO2 hydrosols with an anatase crystal structure had sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 44 publications
2
37
0
1
Order By: Relevance
“…The enhancement of photocatalytic activity due to a synergistic effect of anatase and rutile mixed phases was supported by other experimental evidences [14]. In fact, a controllable phase composition of TiO 2 could be selectively prepared by changing nucleation mode [13], but an amorphous phase usually accompanied with the crystalline phase [9,15]. It is reported that amorphous TiO 2 is nearly inactive due to the facilitated recombination of the photoformed electron and hole [9,16], but one with large surface area and special microstructures is excepted [17].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The enhancement of photocatalytic activity due to a synergistic effect of anatase and rutile mixed phases was supported by other experimental evidences [14]. In fact, a controllable phase composition of TiO 2 could be selectively prepared by changing nucleation mode [13], but an amorphous phase usually accompanied with the crystalline phase [9,15]. It is reported that amorphous TiO 2 is nearly inactive due to the facilitated recombination of the photoformed electron and hole [9,16], but one with large surface area and special microstructures is excepted [17].…”
Section: Introductionmentioning
confidence: 74%
“…The TiO 2 hydrosols could be facilely prepared by using titanium alkoxides and inorganic salts as precursors [5][6][7][8][9]. However, these TiO 2 hydrosols contained a significant amount of impurities which came from the above-mentioned precursors and peptizing agents, such as hydrochloric acid and nitric acid.…”
Section: Introductionmentioning
confidence: 99%
“…1] [ Table 1] To illustrate the trends of changes in crystallinity and particle sizes clearly, the crystallite sizes from XRD results and the average particle sizes from PSD results were calculated and are shown in Table 1. It is clear that the average particle sizes were all much larger than the crystallite sizes due to the slight aggregation of the hydrosol particles, which was mentioned in the pervious work [22]. It was…”
Section: Crystal and Particle Propertiesmentioning
confidence: 72%
“…In particular, the k values for the CH 3 SH degradation were even three times higher than P-25. Our previous study [22] suggested that the TiO 2 hydrosols in comparison with P-25 powder had smaller particle size, more uniform particle size distribution, larger surface area and pore volume, and better transparency. All of these features would contribute to achieve higher photocatalytic activity.…”
Section: Photocatalytic Activitymentioning
confidence: 95%
See 1 more Smart Citation